Usiłowanie nieudolne, usiłowanie nierealne a przestępstwo urojone - Pasternak, Łukasz (Kwartalnik Prawa Publicznego, 2013)
The Author of this article describes one of the institutions of the criminal law, which is inept attempt. Inept attempt is one of forms of commission of an offence. The definition of inept attempt is contained in article 13 § 2 of the Criminal Code. This publication presents the characteristic features of inept attempt. The Author also shows the differences between inept attempt, unreal attempt and imaginary crime (delictum putativum). Knowledge of the differences occurring between those institutions of criminal law is very important from the point of view of the practice use of law. Firstly unreal attempt and imaginary crime are irrelevant in the point of view criminal law, because they are impunity. Secondly when the perpetrator is not himself aware of the fact that committing it is impossible because of the lack of a suitable object on which to perpetrate the prohibited act or because of the use of means not suitable for perpetrating this prohibited act (Article 13 § 2 inept attempt). The court in the case specified in Article 13 § 2 may apply extraordinary mitigation of punishment or even renounce its imposition. The Author also refers to the position of the doctrine and jurisprudence in the matter inept attempt.